Salinity induced redox metabolic shift influence hormonal profile and germination performance of two contrasting indica rice cultivars - Salinity induced redox metabolic shift influence hormonal profile; germination performance of two contrasting indica rice cultivars (Annals of Systems Biology - Peertechz Publications, 2022)
The role of redox deviations under salinity on metabolic dysfunction associated with progression of seed germination is well documented. However, the correlative evaluation of the salinity induced changes in the redox system and hormonal profile in regulating germination are least studied and hence is the subject of present investigation. Imposition of post imbibitional salinity stress (PISS) to two contrasting rice genotypes differing in sensitivity towards salinity (Oryza sativa L., Cultivars Patnai and IR29) caused differential and significant redox-metabolic shift and germination performances. Biomarkers of oxidative stress like, accumulation of total ROS, in situ localization of hydrogen peroxide, radical scavenging property, and lipid peroxidation are assessed for the determination of salinity induced differential changes in redox status of both the experimental cultivars. Salt resistant cultivar Patnai exhibiting better redox regulatory property under PISS in terms of controlled generation of ROS (DCFDA oxidation, H2O2 content) with greater elicitation of total antioxidant capacity (DPPH radical scavenging property), contends lipid peroxidation (accumulation of TBARS) as compared to the salt-sensitive cultivar IR 29. RP-HPLC based estimation of PISS-induced alteration in hormonal pools showed strong correlation between altered redox status (assessed in terms of redox biomarkers) and hormonal profile (endogenous titer of gibberellic acid (GA3), abscisic acid (ABA) and jasmonic acid (JA)) and germination and other physiological phenotypes (t50 value, allocation index, relative water content, and Na+ / K+ ratio) of the experimental rice germplasms, suggesting the influence of differential shift in redox status on germination hormones and early growth performances. Taken as a whole, the work proposes close connection between salinity induced changes in oxidative windows and hormonal profile of germinating seeds, necessary for better management of salinity stress in agriculture.